Migrants, refugees and the Egyptian security state. (2016) - Norman, Kelsey P.
This paper asks why developing countries engage, or not, with their migrant populations, focusing specifically on the Middle East and North Africa (MENA) region. Due to increasingly stringent border controls imposed by traditional migrant-receiving states in Europe and North America and decreasing refugee resettlement rates, hundreds of thousands of migrants and refugees fleeing conflict and poverty in neighbouring African and Arab states have settled in MENA countries. To understand why and how new countries of settlement engage with migrants, this paper uses the case study of Egypt and 59 interviews conducted between September and December 2014 in Cairo and Alexandria. This paper concludes that only some factors from the literature on migration and citizenship are useful in explaining the Egyptian state's engagement with its migrant populations; namely, political economy factors, cultural embeddedness, and host state security interests, though security factors take precedence. To better characterise the type of engagement that Egypt pursues vis-à-vis migrants and refugees, this paper proposes the term 'strategic ambivalence', referring to a policy that aims to neither drive out nor to entirely include migrants and refugees into a host society, but instead aims to maintain the status-quo.